Sustainable lifestyle as practised by Prophet Muhammad S.A.W. / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2021)
The term "sustainability” began to be used more frequently in the 1980s to refer to the way humans live on the planet (Rack, 2014). Yet it is a concept that has existed for as long as people have, to exhibit a concern for the future of our natural resources. Our ancestors were very careful in guarding the natural resources such as jungle produce and fish. Even Prophet Muhammad S.A.W. (Peace Be Upon Him) practised a sustainable lifestyle more than 1400 years ago through his actions and deeds as recorded in the hadith. A balanced diet is one of the cornerstones of good health. When it came to preventing sickness and diseases, Prophet Muhammad S.A.W. advocated eating less as a preventative measure. Miqdam bin Madikarib narrated that the messenger of Allah said, “A human being fills no worse vessel than his stomach. It is sufficient for a human being to eat a few mouthfuls to keep his spine straight. But if he must (fill it), then one third of food, one third for drink and one third for air (Sunan Ibn Majah).” Through the way he performed the ritual ablution, Prophet Muhammad S.A.W. showed the logical approach to sustainable water management. The notion of water conservation is exemplified wisely by the rule that requires us to exercise